Cultivate Islamic identity in emoji design / Muhammad Azmi Kamaruddin - Kamaruddin, Muhammad Azmi (2017)
Motivated by the evolution and rise in smartphones, it is estimated that the instant messaging applications such as WhatsApp, WeChat, and Telegram will continue to growth. One of the abilities in instant messaging applications is the availability of emoji. However, lack of Islamic identity in current emoji has hinder the user especially Muslim to express their daily spiritual activities such as doing prayer, zikr or reading Quran to others. Thus, they are forced to pick an emoji that available in the applications to represent spiritual activities they did. Consequently, the receiver of the message will not understand because emoji that sender are using is not interpreting the right message. Hence, the purpose of this study is to propose a new emoji design based on Islamic spiritual activities and investigates user experience before and after using the Islamic emoji by using survey methodology. The analysis show significant result about the user experience while using the emoji with the aim to increase Muslim remembrance to the God. The result of this study will become a reference to the instant messaging applications developer in order to developing future applications that could satisfy Muslim instant messaging user.